Planning and development of Aunlajore micro-watershed using geo-spatial technique - PAUL, J.C.; SAHU, A.P. (Journal of Soil and Water Conservation, 2023)
Geospatial Techniques like Remote Sensing (RS) and Geographical Information System (GIS) techniques were used for water resource planning of Aunlajore watershed in Sundergarh block of Sundergarh district, Odisha (India). Satellite imagery, toposheet together with field verification were used as the data source for the water resource planning. The objectives of the present research work was to prepare the thematic maps of land use/ land cover, slope and drainage using satellite imagery data and survey of India (SOI) toposheet and to integrate all these maps under GIS environment to prepare the water resource management plans for the study area. Sites for construction of different water conservation structures like water harvesting structures, check dams, farm ponds, percolation tanks, nala bunds, check dams etc. have been identified. These structures will help to create 68015 m3 of storage facility of rain water besides 91 ha and 50 ha irrigation to crops during kharif and rabi season, respectively. The study will be helpful in sustainable development of the natural resources including soil and water of the watershed with the proper implementation of the proposed action plans.